(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Objectives: To assess the clinical presentation and histopathological types and extensions of the disease at the time of presentation. Methods: Cross sectional observational study of 40 patients with sinonasal malignancy from the department of otolaryngology and Head neck surgery, Sylhet MAG Osmani Medical College Hospital, Sylhet Bangladesh, period from May 2019 to April 2020. The patients were examined after admission into hospital pre-operatively and in the postoperative period. The surgical specimens were sent for Histopathology. Results: Majority patients were at 4th to 6th decade where male outnumbered the female with male female ratio was 3.4:1. Out of 40 patients, the majority of patients complaints of nasal obstruction followed by nasal discharge, facial pain, facial swelling and headache. About the site of the lesion maximum patients having the lesion in Maxillary sinus (60%) followed by nasal cavity (15%) multiple sinuses (12.5%) involvement in Ethmoidal sinus (10%) lateral wall of nose (2.5%) Conclusion: Sinonasal Malignancy is usually a disease of middle age and elderly people. Most of the patients (in this study 65% patients come at T3 & T4 stage) presented late with multiple symptoms. Bangladesh J Otorhinolaryngol 2022; 28(1): 37-42